Analisis Kelayakan Usaha Budidaya Udang Vannamei (Litopeneaus Vannamei) Dengan Sistem Semi-Intensif Dan Sistem Intensif Di Kecamatan Brondong Kabupaten Lamongan - Moh Yusuf Dawud (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
Vannamei shrimp farming (lithopenarus vannamei) is one of the alternative solutions to overcome the failure of milkfish cultivation by changing the varieties in the fishery sector, where this species is more resistant to disease. Business analysis and business feasibility in the form of Benefit Cost Ratio (B / C Ratio) Net Benefit Cost Ratio (B / C Ratio), Internal Rate Ratio (IRR), Net Present Valuae (NPV), and Beak Even Point (BEP) calculations. From the results of the analysis showed that the business of shrimp farming vaname declared feasible, with NPV on intensive system the highest value of Rp.46.293.103,45 this means the business is profitable and feasible to be developed. While the NPV on semi-intensive system the highest value of Rp .15.357.758,62 and IRR on semi intensive system 9.98%, while IRR on intensive system 8.19% which means IRR value> MARR, which indicates that this investment is feasible to run. The lowest intensive system value at the time of production / sales volume reaches 3944.28 While in the semi-intensive system the lowest value when the volume of production / sales reached 787.42.BEP selling price on the intensive system the lowest value of Rp.27274.60, while the BEP selling price on semi-intensive system of Rp.24520.58.Hasil calculation of the analysis of the estimated cost increase Operations, decline in prices and the amount of production in the coming year, the business results This is still feasible to run.